Shear strength of concrete beams using stay-in-place flexible formworks with integrated transverse textile reinforcement. (15th November 2022) - Lee, Minu; Mata-Falcón, Jaime; Kaufmann, Walter
Highlights: A new stay-in-place flexible formwork with integrated textile reinforcement was developed and experimentally examined. The integration of high-strength aramid rovings considerably increased the shear strength of the tested concrete beams. Various shear transfer mechanisms were investigated based on refined measurements using DIC and DFOS. High-strength textiles and longitudinal steel bars provided large deformation capacity when bending failure was reached. Abstract: This study investigates the fabrication and the structural performance of concrete beams using weft-knitted tubular fabrics as stay-in-place formworks with integrated textile reinforcement. The use of non-corrosive high-strength textile materials for flexible formworks offers great potential for efficient construction processes and a bespoke design of material-efficient concrete structures. To this end, an experimental campaign consisting of ten three-point bending tests on beams with rectangular cross-sections made with flexible stay-in-place formworks was conducted, where aramid rovings were integrated within the textile as transverse reinforcement to withstand the shear forces while the longitudinal reinforcement consisted of conventional deformed steel bars. The use of digital image correlation measurements and distributed fibre optical sensing allowed the refined analysis of the deformations, including the strains in the textile reinforcement and the estimation of the crack kinematics, which were used to assess various contributions from the reinforcement and the concrete to the shear strength in the governing crack. The amount of textile reinforcement proved to be a decisive parameter in increasing the shear strength, although the full tensile capacity of the rovings could not be exploited due to the lack of ductility in the material behaviour. The thorough consideration of the shear transfer mechanisms revealed a strong dependence of the concrete contribution, specifically aggregate interlock and the formation of a direct strut, on the crack patterns. The combination of the brittle aramid rovings as shear reinforcement and conventional steel reinforcing bars in the tension chord provided a large deformation capacity if the shear reinforcement was able to sustain the load until a bending failure was reached.